What Drives Counter-Extremism? The Extent of P/CVE Policies in the West and Their Structural Correlates - Shanaah, Sadi (Terrorism and political violence, 2023)
Counter-extremism (P/CVE) policies have shot to global prominence rapidly, yet there are large discrepancies in their implementation both between, and inside, countries. In this paper, we construct and present a robust index of P/CVE policies in Western countries (N = 38), based on data submitted by national experts, which we then use to test three hypothesized structural correlates of the extent of P/CVE implementation: threat of terrorism (measured as the number of past attacks/victims), size of Muslim minorities (Muslim communities have been “securitised” as potential threats in the post 9/11 period), and neoliberal governance (drawing on criminological literature that connects neoliberalism to anticipatory crime control). We find the first two structural factors to be positively and significantly correlated to the intensity of P/CVE deployment, while neoliberal governance negatively and significantly. In the discussion, we highlight the usefulness of a complementary in-depth qualitative research inspired by these findings.